Normative data for inferior vena cava diameters and collapsibility index in healthy Indian children from a tertiary care hospital of Chennai - Vidya Ghosh; Suchitra Ranjit; Ramakrishnan Balasubramaniam; Shipra Agrwal (Wolters Kluwer Medknow Publications, 2021)
Background: An ultrasound evaluation of the inferior vena cava (IVC) collapsibility index (CI) has proven to be an excellent noninvasive method of evaluating hydration in adult patients. There is a lack of normative data on the IVC diameters and CI in Indian children. This study was planned to formulate the normative values for IVC diameter in children and adolescents and to assess its correlation with various somatic parameters in Indian children aged 6 months-16 years. Subjects and Methods: Children aged 6 months-16 years in good general health, normal hydrations, and without any significant underlying medical condition who were coming to hospital for their treatment in the outpatient department were consecutively enrolled in the study. The maximum and minimum diameters of IVC were measured during the expiratory and inspiratory phase of the respiratory cycle, respectively, using M mode ultrasonography. CI was also calculated for each subject. These values were correlated with age, gender, and body surface area (BSA). Results: One hundred patients were enrolled in the study, 48 were boys and 52 were girls. The mean (standard deviation) CI was 23.3% (11.9) among males and 20.1% (11.7) among females. The mean maximum and minimum IVC diameter increased significantly with age (r = 0.738, P = 0.00; r = 0.789 P = 0.000) and with BSA (r = 0.73, P = 0.0001; r = 0.77, P = 0.0001). CI did not show significant correlation with age or BSA. Conclusion: IVC dimensions during inspiration or expiration increases with age and BSA, but same relation does not hold for CI. These values were similar among males and females.